Small Terrestrial Mammals - Yee Ling, Chong; Faisal Ali, Anwarali Khan; Andrew Alek, Tuen; Nur Elfieyra Syazana, Hamdan; Nurul Hasni, Sukri; Nur Shyaza Faziella, Mohamad Nahrawi; Qhairil Shyamri, Rosli; Julius William, Dee; Muhd Amsyari, Morni; Badiozaman, Sulaiman; Beatrice Gituen, Langub; Mohd-Azlan, Jayasilan (Natural History Publications (Borneo) Sdn. Bhd., Kota Kinabalu, UNIMAS Publisher, Sarawak Forestry Corporation Sdn Bhd, Kota Samarahan, 2018)
The small terrestrial mammals of Gunung Santubong were documented based on feld data collected using baited cage traps and pitfall traps. Trapping was done at the foot of the mountain and along jungle trails. These areas are publicly accessible and received much human disturbance from nearby forest lodges, beach resorts and rest stations. A total of nine species of small mammals, representing three families— Soricidae (shrew), Muridae (rat), and Sciuridae (squirrel), were recorded. Of these, fve rat species from the family Muridae were captured using bananabaited cage traps. Among them, the Small Spiny Rat (Maxomys baeodon), is rare and endemic to Borneo. It was previously thought to be restricted to northern Borneo, and show a patchy distribution in highland localities in Sabah and north-eastern Sarawak. The threats to this species remain unknown. The species was previously listed as ‘Endangered’ in the IUCN Red List in 1996, and in 2017, was downlisted to ‘Data Defcient’, due to lack of threat information. Another uncommon and locally endemic rat species recorded is Chestnut-Bellied Spiny Rat (Maxomys ochraceiventer). This species was previously recorded from lower montane and dipterocarp forests, from scattered localities in northern Borneo, western Sarawak and east Kalimantan. Both rat species are small in size and have stiff spines on their bodies, which are covered with reddish to brownish fur.